2015
DOI: 10.1039/c5nj01634g
|View full text |Cite
|
Sign up to set email alerts
|

Cajeput tree bark derived activated carbon for the practical electrochemical detection of vanillin

Abstract: Cajeput tree bark derived activated carbon (TBAC) has been prepared and exploited for the electrochemical detection of vanillin (VAN). The physicochemical properties of the TBACs graphitized at different temperatures were characterized using a variety of analytical and spectroscopic techniques, which include X-ray diffraction, field emission-scanning/transmission electron microscopy (FE-SEM/TEM), N 2 adsorption/ desorption isotherm measurements, and thermogravimetric analysis (TGA). Utilized as VAN sensors, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 43 publications
1
23
0
Order By: Relevance
“…The profiles obtained with different KOH mass loading carbonized at different temperatures show similar behaviour between room temperature to 1000 °C and as such, a single profile is reported here. These TGA results are also similar to earlier studies on tree bark materials reported by Veeramani and co-workers [28]. Fig.…”
Section: Morphological and Structural Characterizationsupporting
confidence: 92%
See 2 more Smart Citations
“…The profiles obtained with different KOH mass loading carbonized at different temperatures show similar behaviour between room temperature to 1000 °C and as such, a single profile is reported here. These TGA results are also similar to earlier studies on tree bark materials reported by Veeramani and co-workers [28]. Fig.…”
Section: Morphological and Structural Characterizationsupporting
confidence: 92%
“…5a. This revealed two distinct regions of significant weight loss at 85-100 °C and 650-670 °C which correspond to the desorption of physisorbed water and carbon pyrolysis, respectively [28] with 60% of its weight still present at 1000 °C. The profiles obtained with different KOH mass loading carbonized at different temperatures show similar behaviour between room temperature to 1000 °C and as such, a single profile is reported here.…”
Section: Morphological and Structural Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Porous activated carbon (PAC)-related materials offer great advantages for practical applications 1 2 , such as adsorbents, energy storage, catalyst supports, and electrodes for fuel cells 3 . Moreover, owing to the intrinsic properties, such as high surface area, diversified morphology, good electrical conductivity, and tailorable porosity, PACs are also favorable materials as supports for metal nanoparticles (NPs) or metal oxides, and have been widely applied as biomolecule sensors 13 14 15 , biomedical engineering materials 16 , toxic molecules/heavy metal detectors 17 18 , and supercapacitors 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 . In terms of the latter, aside from the widely studied carbon materials such as graphene 34 35 36 37 38 , carbon nanotubes 37 38 39 40 , and ordered mesoporous carbons 41 42 43 44 , PACs are easy to prepare, eco-friendly, and cost-effective; they may be prepared from renewable biomass precursors through facile carbonization and activation routes, for examples, from tree barks or leaves 18 20 21 22 23 24 , plants 25 26 , fruits 27 28 , grain or seed shells 29 30 31 32 45 46 47 48 49 50 51 , lignin 52 53 , food derivatives 54 , marine products 33 , and so on.…”
mentioning
confidence: 99%
“…As will be shown later that the presences of these micro-and meso-porosities, which facilitate rapid transport of electrolyte ions during the oxygen reduction reaction (ORR) process, are responsible for the superior electrochemical and electrocatalytic performances of the HA-GCNs materials [2,29,30]. It is noteworthy that mesoporous carbon nanosheets have been widely employed as electrode and catalyst support materials for supercapacitors and fuel cells [3,17,[31][32][33].…”
Section: Resultsmentioning
confidence: 99%